EXTENSION AND COMMUNICATION IN THE INTEGRATED MANAGEMENT STRATEGY FOR THE SUSTAINABLE DEVELOPMENT OF KONAWE COASTAI, AREA SOUTHEAST SULAWESI(Penyuluhan dan Komunikasi dalam Strategi Pengelolaan Terpadu Mewujudkan Pembangunan Berkelanjutan Wilayah Pesisir) - Mahmud Hamundu; Abdul Manan (Jurnal Manusia dan Lingkungan, 2004)
ABSTRACTA project entitled the Extension and Communication in Integrated Management Strategy for the Sustainable Development of Konawe District has been implemented at western part of Konawe coastal area. lt was started as a pilot project from March 20OZ to March 2004. The goal of the project are to improve ecological and economic function of land, coral reef and mangrove forest at Konawe coastal zone, so that the productivity of agriculture, fish and other marine biota as well as community income are increased. The out put achieved are (1) A preperation of Document of Sustainable Development of Westem Coastal of Konawe District, (2) rehabilitation of 200 ha of degraded mangrove forest, (3) establishment of Local Economic lnstitution (called ELKAM) to provide capital for local community. The membership had been growing fast, from 50 members in 2002 and increased to about 750 members in 2004. The initial results are that by practicing a good extension with appropriate communication tools is the best approach for integrated coastal management strategy of Konawe District. ABSTRAKSebuah proyek berjudul Peranan penyuluhan dan komunikasi dalam strategi pengelolaan terpadu mewujudkan Pembangunan Berkelanjutan di Wilayah Pesisir Kabupaten Konawe telah dilaksanakan dari Maret 2002 sampai Maret 2004. Tujuan proyek adalah memperbaiki fungsi ekologi dan ekonomi terhadap lahan, hutan bakau, terumbu karang, sehingga produktivitas pertanian, ikan dan biota laut lainnya serta pendapatan masyarakat meningkat. Hasil yang diperoleh adalah (1) telah disusun dokumen Pembangunan Berkelanjutan Wilayah Pesisir bagian Barat Kabupaten Konawe, (2) Seluas 200 kawasan hutan bakau telah direhabilitasi, (3) telah dibentuk Lembaga Keuangan Masyarakat (ELKAM), anggotanya berkembang pesat yaitu dari 50 anggota tahun 2002 menjadi 750 anggota tahun 2004. Kesimpulan awal menunjukkan bahwa penyuluhan yang baik dengan komunikasi yang sesuai merupakan pendekatan yang tepat dalam pengelolaan wilayah pesisir terpadu di Kabupaten Konawe.